THE INHALATION OF ACTIVE PHARMACEUTICAL INGREDIENTS AND ITS PHARMACEUTICAL STUDIES - C Kumaresan (Journal of Global Pharma Technology, 2016)
The aerosols such as gas borne suspension of solid or liquid particles are used for therapeutic applications of lung and other systemic diseases. These inhaled pharmaceutical aerosols deliver drug (active pharmaceutical ingredient) to the alveolar region to the blood in the capillaries. The injectable drugs are significantly administered by inhalation. There are so many drug delivery systems of inhaled pharmaceuticals are available. The metered dose inhaler, dry powder inhaler and nebulizers drug delivery systems are most famous. The development of suitable drug delivery system of inhaled pharmaceuticals for new drugs is very simple at this modern times technology. This review deals about inhaled pharmaceutical aerosols and its studies including particle size and adhesive forces of aerosol particles.Keywords: Dry powder inhaler, pharmaceutical inhalation, drug delivery, lung